ANALISIS SIKAP DISIPLIN PADA MATA KULIAH GEOMETRI DASAR MENGGUNAKAN MODEL PEMBELAJARAN KONTEKSTUAL BERBASIS ETNOMATEMATIKA - Maria Fatima Mei; Stefania Baptis Seto; Stefanus Notan Tupen (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
The purpose of this study was to analyze student discipline attitudes using an ethnomathematical-based contextual learning model. The sample in this study was the second-semester students of the Mathematics Education Study Program at the University of Flores totaling 29 people. This study uses survey and correlational methods. The instrument used is a questionnaire consisting of 40 statements based on indicators of student discipline attitudes. The results showed that the use of ethnomathematical-based contextual learning models obtained an average percentage of 62, 44% in the high category. This means that there is a positive influence of disciplined attitudes on ethnomathematical-based contextual learning.